Replicative senescence as a barrier to human cancer. (February 2000) - Parkinson, E. K.; Munro, J.; Steeghs, K.; Morrison, V.; Ireland, H.; Forsyth, N.; Fitzsimmons, S.; Bryce, S.
Abstract : There is evidence that one critically short telomere may be recognized as DNA damage and, as a consequence, induce a p53/p21 WAF - and pl6 INK4A -dependent G1 cell cycle checkpoint to cause senescence. Additionally, senescence via a p53-and pl6 INK4A -dependent mechanism can be induced by the over- or under-stimulation of certain signalling pathways that are involved in cancer. Central to this alternative senescence mechanism is the pl4 ARF protein, which connects oncogene activation, but not DNA damage, to p53 activation and senescence. We find that immortal keratinocytes almost invariably have dysfunctional p53 and p16 and have high levels of telomerase, but very often express a wild-type pl4 ARF . Furthermore, when normal keratinocytes senesce they show a striking elevation of p16 protein, but not of p14 ARF or its downstream targets p53 and p21 WAF . These results suggest that p16, rather than pl4 ARF, is the more important gene in human keratinocyte senescence, but do not exclude a co-operative role for pl4 ARF, perhaps in the induction of senescence by activated oncogenes in neoplasia. Regardless of mechanism, these results suggest that replicative senescence acts as a barrier to human cancer development.